The impact of foreign direct investment and venture capital investment on entrepreneurship in the Republic of Serbia - Jolović, Ivana; Lošonc, Alpar (Eastern Review, 2019)
The subject of the research is the examination of features and significance of two modern types of investment intended for financing entrepreneurship: that is, foreign direct investment and venture capital investment. The starting point of the study is the sector of small and medium-sized enterprises and entrepreneurs with all the challenges and opportunities that characterize its financial position in the Republic of Serbia. The aim of this research is to analyse the impact of both direct investment and entrepreneurial capital investment on small businesses, or more precisely, to examine the influence of foreign direct investment and venture capital investment on entrepreneurship. This paper focuses on the impact that these types of financing have on management, financial stability, and the performance of the relevant business entities. Furthermore, the current situation and perspectives of these types of financing are analysed in detail. The aim of this paper is to provide insight into the effects that foreign direct and venture capital investments have on Serbian small and medium-sized enterprises and the entrepreneurial sector, as well as to point to what is currently the more favourable solution for the financing problem with which these entities are faced. The following methods are used for the preparation of this paper: a detailed analysis of the content of European and national statistical reports; available national and foreign literature of international and domestic authors in the field of foreign direct investment, venture capital investment and entrepreneurship; descriptive and comparative methods.